The Linkage Between Arctic Sea Ice and Midlatitude Weather: In the Perspective of Energy. Issue 20 (30th October 2018) - Gu, Sen; Zhang, Yang; Wu, Qigang; Yang, Xiu‐Qun
Abstract: The influence of Arctic changes on the weather in the highly populated midlatitude is a controversial topic with little agreements regarding its existence or its mechanism. Utilizing eddy energy as metrics of circulation and temperature fluctuations with weather patterns, this study highlights the robust relationship between the early autumn Arctic sea ice and the wintertime transient activities over northern Eurasia on interannual time scale, by comparing groups of statistical and diagnostical results. With the reduction of sea ice in early autumn in Barents, Kara, Laptev, and East Siberia Seas, the atmosphere over those polar regions exhibits significant increase in eddy energy in the following winter. In the adjacent Eurasia, the wintertime synoptic eddy energy decreases, while the low‐frequency eddy energy, corresponding to persistent weather patterns, exhibits evident and dominant increase. The enhanced southward energy propagation of low‐frequency waves from the polar region to the north of middle‐to‐east Asia suggests a mechanism for the Arctic‐midlatitude linkage, indicating that Arctic sea ice could be a source of predictability for both extended‐range and subseasonal to seasonal forecasts. Plain Language Summary: The Arctic is warming and melting at rapid rate, while its influence on the weathers in the highly populated midlatitude is a controversial topic, with little agreements regarding its existence or its mechanism. Objective metrics from the perspective of atmospheric dynamics and sophisticated diagnostics are exceedingly needed to quantify and understand the Arctic‐midlatitude linkage.This study proposes to use eddy energy as an objective and dynamical meaningful metric of circulation change with weather patterns and finds robust linkage between the Arctic change and eddy energy in Northern Eurasia by comparing groups of statistical and diagnostical results. With the decrease of Arctic sea ice, the change of eddy energy shows that the persistent weathers and quasi‐stationary wave activity increase significantly but synoptic activities decrease. A mechanism for such linkage is also identified by checking the eddy energy propagation. The results suggest a future pathway to quantify and understand the Arctic‐midlatitude linkage via diagnosing energetics and the budget, transfer, and teleconnection of eddy energies. The results also show that Arctic sea ice could be a source predictability for both extended‐range and subseasonal to seasonal forecasts. Key Points: Utilizing eddy energy as metrics, a robust linkage is identified between Arctic sea ice and midlatitude weather pattern within seasonal time scale Eddy energy corresponding to persistent winter weather significantly increases in northern Eurasia with autumn Arctic sea ice loss The southward propagation of low‐frequency waves from the polar region plays a key role for the linkage